Cyst Nematode Parasitism Induces Dynamic Changes in the Root Epigenome. Issue 1 (15th March 2017) - Hewezi, Tarek; Lane, Thomas; Piya, Sarbottam; Rambani, Aditi; Rice, J Hollis; Staton, Meg
Abstract : Plant-parasitic cyst nematodes induce extensive changes in DNA methylation patterns that impact the expression of Arabidopsis genes required for nematode parasitism. Abstract: A growing body of evidence indicates that epigenetic modifications can provide efficient, dynamic, and reversible cellular responses to a wide range of environmental stimuli. However, the significance of epigenetic modifications in plant-pathogen interactions remains largely unexplored. In this study, we provide a comprehensive analysis of epigenome changes during the compatible interaction between the beet cyst nematode Heterodera schachtii and Arabidopsis ( Arabidopsis thaliana ). Whole-genome bisulfite sequencing was conducted to assess the dynamic changes in the methylome of Arabidopsis roots in response to H. schachtii infection. H. schachtii induced widespread hypomethylation of protein-coding genes and transposable elements (TE s), preferentially those adjacent to protein-coding genes. The abundance of 24-nt siRNAs was associated with hypermethylation of TE s and gene promoters, with influence observed for methylation context and infection time points. mRNA sequencing revealed a significant enrichment for the differentially methylated genes among the differentially expressed genes, specifically those with functions corresponding to primary metabolic processes and responses to stimuli. The differentially methylated genes overlapped with more than one-fourth of the syncytium differentially expressed genes and are of functional significance. Together, our results provide intriguing insights into the potential regulatory role of differential DNA methylation in shaping the biological interplay between cyst nematodes and host plants.